Adrenomedullin Expression Is Associated With the Severity and Poor Prognosis of Interstitial Lung Disease in Dermatomyositis Patients - Ye, Lifang; Zuo, Yu; Chen, Fang; Xu, Yuetong; Zhang, Puli; Yang, Hongxia; Peng, Qinglin; Wang, Guochun; Shu, Xiaoming (Frontiers in Immunology, 2022)
Objective We sought to evaluate adrenomedullin mRNA levels in the peripheral blood mononuclear cells (PBMCs) of patients with dermatomyositis (DM) as well as their correlation with the severity of interstitial lung disease (ILD). Methods A total of 41 DM patients, 7 immune-mediated necrotizing myopathy (IMNM) patients, were recruited, in addition to 21 healthy controls (HCs). The adrenomedullin mRNA levels in PBMCs were measured via quantitative reverse-transcription real-time polymerase chain reaction (qRT-PCR). The associations of expression levels with major clinical, laboratory, pulmonary function parameters, and the prognosis of patients with DM-related ILD (DM-ILD) were also analyzed. In addition, immunohistochemical analysis of adrenomedullin was performed on lung tissues from DM-ILD. Results Compared with IMNM patients and HCs, adrenomedullin mRNA levels in PBMCs were significantly higher in DM patients (p = 0.007 and p<0.001, respectively). Among DM patients, the levels were significantly higher in those with rapidly progressive ILD(RP-ILD) than in those with chronic ILD (p = 0.002) or without ILD (p = 0.003). The adrenomedullin mRNA levels in DM-ILD were positively correlated with serum ferritin (r =0.450, p =0.008), lactate dehydrogenase (LDH) (r =0.373, p =0.032), and lung visual analog scale (VAS) (r=0.354, p=0.039) while negatively associated with pulmonary function test parameters, including the percent predicted forced expiratory volume in one second (r = -0.592, p = 0.003), percent predicted forced vital capacity (r = −0.496, p = 0.036), and percent predicted carbon monoxide diffusion capacity (r = -0.505, p = 0.032). Immunohistochemical analysis of adrenomedullin confirmed higher expression in the alveolar epithelial cells and macrophages of DM patients with RP-ILD. Among the DM patients with ILD, six decedents exhibited higher adrenomedullin levels than 28 survivors (p = 0.042). The cumulative survival rate was significantly lower (57.1% vs. 100%, P = 0.001) in patients with an adrenomedullin level > 0.070 than in those with levels <0.070.